A framework for involving coproduction partners in research about young people with type 1 diabetes. (10th December 2021) - Desborough, Jane; Parkinson, Anne; Lewis, Fiona; Ebbeck, Harry; Banfield, Michelle; Phillips, Christine
Abstract: Background: Involvement of end‐users in research can enhance its quality, relevance, credibility and legitimacy; however, the processes through which these changes occur are unclear. Our aim was to explore a coproduction research team's experiences of their involvement in research about young people with type 1 diabetes mellitus (T1DM). Methods: Semi‐structured interviews conducted with two young people with T1DM, two parents, one diabetes educator, one endocrinologist‐scientist and one research‐engineer explored experiences of coproduction research and its impact on both the research and the participants. Drawing on grounded theory, we undertook inductive analysis and storyline mapping to develop a theorized framework of mechanisms supporting the process of coproduction in T1DM research with young people. Findings: The framework involving coproduction partners in research about young people with type 1 diabetes centres on the unique expertize that different team members bring to the research and describes conditions that enable expert contributions through the enactment of a variety of expert roles . The framework also describes outcomes —the impact of the expert contributions on both the research and the team members involved. Conclusion: The findings of this small exploratory study provide a sound foundation to develop further understanding about structures and processes that are integral for the success of coproduction research teams. The framework may provide a guide for researchers planning to incorporate coproduction, on elements that are important for this model of research to succeed. It may also inform coproduction impact assessment research and be used for hypothesis testing and expansion in future studies.